(untitled) - Craigo, Sabrina D. (New York, 2005)
Perfect for providing expert care for disorders created or affected by pregnancy. Each disorder-focused chapter opens with a high-yield “pathway” summarizing the best course of action as determined by scientific studies. Useful illustrative case studies, tips, clinical forms, and patient education information are included
Keywords: Pregnancy,Sụ mang thai; Complications,Biến chứng